A Case Report of Occult Breast Cancer Detected by Diagnostic Laparoscopy for Suspected Ovarian Cancer - Arisa Egami; Yosuke Tarumi; Ayaka Okamura; Kohei Aoyama; Hisashi Kataoka; Tetsuya Kokabu; Kaori Yoriki; Fumitake Ito; Taisuke Mori (Hindawi Limited, 2024)
Diagnostic laparoscopy is useful in the management of gynecological cancers; however, it can occasionally result in the detection of other malignancies. Occult breast cancer (OBC) is metastatic breast cancer without a recognized primary breast lesion. We report a rare case of OBC that was detected laparoscopically. A 64-year-old female presented to our hospital with back pain. Magnetic resonance imaging (MRI) revealed a 50 mm multicystic tumor with an internal nodule in the right ovary. Positron emission tomography/computed tomography showed abnormal accumulation in multiple lymph nodes, moderate accumulation in the ovarian tumor nodule, and no accumulation in the breasts. Ovarian cancer was suspected, and a diagnostic laparoscopy was performed. Laparoscopically, a cystic tumor in the right ovary and 10 mm nodule in the right round ligament were observed and partially resected. Immunohistopathologically, the nodules of the round ligament exhibited features consistent with those of breast cancer, but the ovarian tumor was a seromucinous borderline tumor. MRI revealed no breast lesions. Therefore, the malignancy was diagnosed as an OBC.